The efficacy of traditional Chinese Medical Exercise for Parkinson's disease: a systematic review and meta-analysis. - Yan Yang; Wei Qing Qiu; Yan Lei Hao; Zhan Yun Lv; Shu Ji Jiao; Jun Feng Teng (PLoS ONE)
Background and objective Several studies assessed the efficacy of traditional Chinese medical exercise in the management of Parkinson's disease (PD), but its role remained controversial. Therefore, the purpose of this systematic review is to evaluate the evidence on the effect of traditional Chinese medical exercise for PD. Methods Seven English and Chinese electronic databases, up to October 2014, were searched to identify relevant studies. The PEDro scale was employed to assess the methodological quality of eligible studies. Meta-analysis was performed by RevMan 5.1 software. Results Fifteen trials were included in the review. Tai Chi and Qigong were used as assisting pharmacological treatments of PD in the previous studies. Tai Chi plus medication showed greater improvements in motor function (standardized mean difference, SMD, -0.57; 95% confidence intervals, CI, -1.11 to -0.04), Berg balance scale (BBS, SMD, -1.22; 95% CI -1.65 to -0.80), and time up and go test (SMD, -1.06; 95% CI -1.44 to -0.68). Compared with other therapy plus medication, Tai Chi plus medication also showed greater gains in motor function (SMD, -0.78; 95% CI -1.46 to -0.10), BBS (SMD, -0.99; 95% CI -1.44 to -0.54), and functional reach test (SMD, -0.77; 95% CI -1.51 to -0.03). However, Tai Chi plus medication did not showed better improvements in gait or quality of life. There was not sufficient evidence to support or refute the effect of Qigong plus medication for PD. Conclusions In the previous studies, Tai Chi and Qigong were used as assisting pharmacological treatments of PD. The current systematic review showed positive evidence of Tai Chi plus medication for PD of mild-to-moderate severity. So Tai Chi plus medication should be recommended for PD management, especially in improving motor function and balance. Qigong plus medication also showed potential gains in the management of PD. However, more high quality studies with long follow-up are warrant to confirm the current findings.